Synthesis of minoxidil conjugates and their evaluation as HL-60 differentiation agents. Issue 4 (15th February 2016) - Stoica, Sonia; Magoulas, George E.; Antoniou, Antonia I.; Suleiman, Sherif; Cassar, Analisse; Gatt, Lucienne; Papaioannou, Dionissios; Athanassopoulos, Constantinos M.; Schembri-Wismayer, Pierre
Graphical abstract: Abstract: Activation of minoxidil (MNX) with N, N ′-carbonyldiimidazole and coupling with natural polyamines (PAs) and commercially available aliphatic or aromatic amines provided a series of new conjugates which were evaluated for their ability to induce differentiation to HL-60 acute myeloid leukemia cancer cells, using a modified NBTZ reduction test. Although neither MNX nor 4, 4′-methylenedianiline (MDA) or 2, 7-diaminofluorene (DAF), alone or in combination, had any effect, the MNX-spermine (SPM) conjugate (11 ) and the conjugates7 and8 of MNX with MDA and DAF exhibited a differentiation-inducing effect at a concentration of 10 μM without being toxic on proliferating human peripheral blood mononuclear cells.